Correction: Highly efficient, all-solution-processed, flexible white quantum dot light-emitting diodes. Issue 45 (17th November 2020) - Shen, Piaoyang; Li, Xiaomin; Cao, Fan; Ding, Xingwei; Yang, Xuyong
Abstract : Correction for 'Highly efficient, all-solution-processed, flexible white quantum dot light-emitting diodes' by Piaoyang Shen et al., J. Mater. Chem. C, 2018, 6, 9642–9648, DOI: ; 10.1039/C8TC03155J .